Transformation der Siedlungswasserwirtschaft – Steuerungsmechanismen im Diskurs ressourcenorientierter Systemansätze am Beispiel von Thüringen - Wolf, Mario; Londong, Jörg (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
New sanitary systems are an intelligent way to approach wastewater management in the face of demographic and climatic changes. It is also compatible with the emerging paradigm of a resource-oriented management of wastewater. While the general technical applicability of resource-oriented systems has been proven in various projects, the realisation is still on hold. The reasons can be found in several risks for wastewater disposal companies that are linked to the implementation process. Based on an analysis of the general context of an implementation of a new sanitary system in a typical rural area of Eastern Germany, this paper analyses to which extend the implementation of such innovative approaches can be facilitated by the regulation system and which steps need to be taken. According to this aim, risks that can hamper the transformation of the wastewater sector are identified, major administrative controlling mechanisms outlined and depicted in which strategic approach these could be used in order to foster the implementation of resource-oriented sanitary systems. As a result, the feasibility of the implementation of new alternative sanitary systems through the strategic application of the controlling mechanisms is generally proven. However, collaborations of the wastewater sectors with stakeholders of other sectors are required.